Overtraining and Burnout: The Hidden Toll of Professional Sports on Athlete Health - Grzelak, Alicja; Langner, Sara (Quality in Sport, 2024)
Introduction: Professional sports demand exceptional physical and mental dedication, yet the intensive training and competitive pressures can often lead to overtraining and burnout among athletes. These phenomena not only compromise athletic performance but also pose significant risks to long-term physical and mental health, raising concerns within the sports and medical communities. Purpose of Work: This study explores the hidden toll of overtraining and burnout on professional athletes, examining their effects on physical health, psychological well-being, and career longevity. It aims to highlight underlying causes, consequences, and strategies for prevention and intervention. State of Knowledge: Existing research identifies overtraining syndrome as a key contributor to chronic fatigue, decreased performance, and vulnerability to injury. Burnout, often stemming from emotional exhaustion and depersonalization, is linked to anxiety, depression, and withdrawal from sports. Despite growing awareness, gaps remain in comprehensive strategies to mitigate these challenges, particularly in integrating mental health support within training programs. Material and methods: The study utilized a systematic review approach, searching across well-known academic databases like PubMed and Google Scholar, and then carefully screening the results to select pertinent studies for detailed examination. Summary: This paper synthesizes the current research on overtraining and burnout, outlining the challenges faced by athletes and the common physical and mental health issues they confront. The findings underscore the need for proactive interventions, such as customized training schedules, psychological support, and comprehensive education programs for both athletes and coaches.